2022
DOI: 10.18280/mmep.090315
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Information Extraction Techniques, Models and Systems

Abstract: The present article aims to review and evaluate the practiced and classical techniques, tools, models, and systems concerning automatic information extraction (IE) from published scientific documents like research articles, patents, theses, technical reports, and case studies etc. IE is performed for various reasons such as better indexing, archiving, searching, and retrieving. That is mainly used by the search engines and the indexing services as well the digital libraries and semantic web. In this regard, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Rahman et al [26] and Zaman et al [27] presented assessment of information extraction approaches, model, and techniques by surveying more than a decade literature in the area. In this regard, they performed a comprehensive and systematic literature review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rahman et al [26] and Zaman et al [27] presented assessment of information extraction approaches, model, and techniques by surveying more than a decade literature in the area. In this regard, they performed a comprehensive and systematic literature review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A possible explanation is the more professional words typically used in the first two. It is commonly observed that precision, recall, and F-measure [69,70] are among the most widely used criteria to evaluate the performance of deep learning approaches as shown in the last rows of Table 4.…”
Section: Deep Learning-based Approachesmentioning
confidence: 99%
“…The moment these mentioned set of signals are transmitted over a frequency nonselective Rayleigh flat fading channel as utilized in several studies in the literature for similar type of the assumed OFDM systems [41][42][43][44][45][46][47][48], the received equivalent low pass signal can be written as:…”
Section: Channelmentioning
confidence: 99%